Review of performance measurement: Implications for public–private partnerships - Liu, J.; Love, Peter; Smith, J.; Regan, M.; Palaneeswaran, E. (Emerald Group Publishing Ltd., 2015)
Purpose – The purpose of this paper is to review the normative literature in regard to public-private partnerships (PPPs) and their evaluations, and attempts to investigate whether the Performance Prism is a feasible framework for effective PPP performance measurement. Design/methodology/approach – An in-depth and critical literature review is conducted in this study. Discussion concentrates on PPP features, performance measurement in PPPs, performance measurement in construction, and characteristics of the Performance Prism. Findings – The Performance Prism exhibits a strong ability to capture the distinct features of PPP infrastructure projects and can be considered as a framework suitable for effective and efficient performance measurement. Practical implications – It is essential that stakeholders have a feasible performance measurement framework to effectively measure performance as they embark on PPP infrastructure projects. This paper can be used as a theoretical base and conceptual framework capable of assisting in the design and selection of effective performance measures for PPPs. Originality/value – Many governments across the world use PPPs to procure public assets owing to the scarce funds available for infrastructure development. Effective performance measurement is critical to the successful delivery of a PPP project. Conventional ex post evaluation that solely focuses on meeting budget and predetermined project duration is being widely used to measure PPPs in practice. PPPs are more complicated than traditional procurement due to their multiple stakeholder integrations and long-term processes. However, the research on effective PPP performance measurement is limited for addressing such vital issues, and this paper attempts to bridge this knowledge gap.